Survey of volatility and spillovers on financial markets - Evžen Kočenda (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2017)
In this survey article, we present a rich extent of literature on volatility and its propagation on financial markets via spillovers. We document how new approaches or improved existing methodologies lead to results that offer richer insights than those derived from standard econometric techniques. Moreover, the implications of the results can be related to a wide set of markets as the surveyed articles cover emerging and developed European markets as well as the United States.
urn:nbn:de:101:1-201703141253
Keywords: C10; E44; F31; G15; 330; volatility; volatility spillovers; financial markets